Digital addiction and the academic performance among universities’ students / Lailatul Faizah Abu Hassan …[et al.] - Abu Hassan, Lailatul Faizah; Rochin Demong, Nur Atiqah; Mohd Salleh, Mohammad Zaim; Omar, Emi Normalina; Alwi, Anisah (Universiti Teknologi MARA, 2021)
Digital addiction has been called digital dependency and digital compulsive. By any name, it is a compulsive behavior that completely dominates the addict’s life. Digital addicts make the digital technology a priority more important than family, friends, and work. The digital technology becomes the organizing principle of addicts’ lives. The purpose of this study is to identify the relationship between Digital Addiction (DA) and academic performance among college students in public and private university. This study also identified the differences in digital addiction in terms of gender. The statistical techniques frequency and percentage are used to identify the patterns of using the Internet; t-test and one-way ANOVA is used to examine the differences in DA in terms of demographic factors. Pearson correlation technique will also be used to determine the relationship between DA and academic performance. This study helps to determine the level of digital addiction among college student and how its impacts their academic performance.